Pengaruh Citra Merek Terhadap Keputusan Pembelian Benih Cabai Merah - Sucipto, Ossy Alfiani; Saidah, Zumi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Red chili is one of the leading horticultural commodities with significant economic value, making it widely cultivated by farmers. The high demand for red chili seeds among farmers has led to the emergence of various seed brands in the market. Increasingly intense business competition drives companies to optimize their best product outcomes. A good brand image can provide farmers with confidence that the seeds have high quality, durability, and satisfactory yields. This influences farmers' preferences in deciding which brand of red chili seeds to purchase. This research aims to determine the influence of brand image on the purchase decision of red chili seeds. The study involved 100 red chili farmers in the Pasirwangi District as respondents. The analysis used includes classical assumption tests to examine the questionnaire items and simple linear regression tests to determine whether brand image affects the purchase decision. The results of this study show that there is a significant influence of brand image on the purchase decision of red chili seeds by farmers in the Pasirwangi